The Bibliography of Articles of the Republican Era 1923-1999: A Critical Review - Yaşar Tonta; Umut Al (Türk Kütüphaneciliği)
The Turkish National Library has recently published the Bibliography of Articles of the Republican Era 1923-1999 (BARE) on CD-ROM. BARE is the most comprehensive bibliography that indexes the articles contained in Turkish journals received by the Library through “legal depot”. It contains bibliographic information on a total of566,627 articles that appeared in 4,418 Turkish journals andperiodicals. This paper critically reviews the Bibliography on the basis of its user interface, database design and data quality. Human-computer interaction (HCI) issues and the usability criteria seem to have not been taken into account when designing the user interface of the BARE CD-ROM. The user interface is not intuitive. It appears that a comprehensive systems analysis study was not carried out before designing the database and the principles of database management design seem to have been ignored. Bibliographic data listed in the printed copies of the Bibliography was simply transferred to a flat table, which resulted in data redundancy and waste of space. Boolean searches cannot be performed on author and article titles. Nine percent of the records contained errors in article and journal titles as well as authors’ names. Used through the web site of the Turkish National Library, the Bibliography and its interface should be redesigned and improved, and the functions of the search engine should be increased.